Volatility Spillover among CDS, Equities and Bonds during the 2007-2010 financial crisis: Evidence from the U.S. Market. - Bozhidarov, Kaloyan (2011)
This study examines the volatility transmission between credit default swap (CDS), bonds and equities for U.S. corporate entities during the recent financial crisis. The study sample covers the 2005-2010 period and is separated in two parts – pre-crisis period and crisis period. The separation of the data in two samples is made to facilitate the comparison between the two periods and to provide evidence of the behavior of the three markets in different credit conditions. The paper utilizes the GARCH-BEKK model and finds evidence of relatively limited volatility transmission during the pre-crisis period mainly from the CDS and equity markets to the bond market. In contrast, during the financial crisis the linkage between the three markets has increased dramatically, with bilateral volatility transmission between all three markets. A further analysis is carried out to investigate the causes for this strong volatility transmission during the crisis period. The companies from the sample are separated in two sub samples – bad potential companies and good potential companies. The main finding is that volatility spillover for bad potential companies is very high, while for good potential companies it is very low. Overall, the strong linkage between the markets that is found in the crisis period implies that none of the markets incorporates new credit information more efficiently than the others. Thus, the main implication of the study is that investors, market participants and regulators should look into all three markets for signs of changing credit conditions. In addition, the limited volatility spillover for good potential companies during the crisis period implies that even though the correlation between markets has increased market participants can still find investments that offer diversification. Keywords: Credit Default Swap, Volatility Transmission, GARCH-BEKK, Financial crisis.